Challenges of Integrating APOL1 Genetic Test Results into the Electronic Health Record - Rasmussen, Luke V.; Agrawal, Akansha H.; Botsford, Paul; Powers, Andrew; Schnoebelen, Jeffrey; Xinos, Stavroula; Harper, Gail; Thanner, Jane; McCabe, Sarah; Moore, Stephen; Wicklund, Catherine A.; Duquette, Debra; Gordon, Elisa J. (Applied Clinical Informatics, 2023)
Objectives Integrating genetic test results into the electronic health record (EHR) is essential for integrating genetic testing into clinical practice. This article describes the organizational challenges of integrating discrete apolipoprotein L1 (APOL1) genetic test results into the EHR for a research study on culturally sensitive genetic counseling for living kidney donors.Methods We convened a multidisciplinary team across three institutions (Northwestern University, Northwestern Memorial HealthCare [NMHC], and OHSU Knight Diagnostic Laboratories [KDL]), including researchers, physicians, clinical information technology, and project management. Through a series of meetings over a year between the team and the genetic testing laboratory, we explored and adjusted our EHR integration plan based on regulatory and budgetary constraints.Results Our original proposal was to transmit results from KDL to NMHC as structured data sent via Health Level Seven (HL7) v2 message. This was ultimately deemed infeasible given the time and resources required to establish the interface, and the low number of samples to be processed for the study (n = 316). We next explored the use of Epic's Care Everywhere interoperability platform, but learned it was not possible as a laboratory test ordered for a research study; even though our intent was to study the APOL1 genetic test result's clinical use and impact, test results were still considered “research results.” Faced with two remaining options—downloading a PDF from the KDL laboratory portal or scanning a faxed result from KDL—only a PDF of the APOL1 test result could be integrated into the EHR, reinforcing the status quo.Conclusion Even with early and ongoing stakeholder engagement, dedicated project management, and funding, unanticipated implementation challenges—especially for research projects—can result in drastic design tradeoffs.
Keywords: Research; clinical laboratories; information systems; living donation; apolipoprotein L1